(untitled) - Henkes, Kevin (New York, NY, 2010)
After helping her mother weed, water, and chase the rabbits from their garden, a young girl imagines her dream garden complete with jellybean bushes, chocolate rabbits, and tomatoes the size of beach balls.
Structure demand: 79 (high)
Syntactic demand: 92 (very high)
Decoding demand: 77 (high)
AD570L
Semantic demand: 49 (medium)
Accelerated Reader AR
Keywords: Gardens; Picture books; Fiction; Imagination; Fiction; Gardens; Juvenile fiction; Imagination; Juvenile fiction; Picture book